2008
DOI: 10.1590/s1516-89132008000700033
|View full text |Cite
|
Sign up to set email alerts
|

Biodistribution of the radiopharmaceutical technetium-99m-sodium phytate in rats after splenectomy

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Besides the disease, these procedures could be altered by medications, surgery and natural products that could change the biodistribution of radiopharmaceuticals in a specific target or the fixation of Tc to blood constituents 16,18 . In general, the labeling of blood constituents could decrease by the action of …”
Section: Discussionmentioning
confidence: 99%
“…Besides the disease, these procedures could be altered by medications, surgery and natural products that could change the biodistribution of radiopharmaceuticals in a specific target or the fixation of Tc to blood constituents 16,18 . In general, the labeling of blood constituents could decrease by the action of …”
Section: Discussionmentioning
confidence: 99%
“…The radiopharmaceutical 99mTc-phytate is used as evidence of hepatic function and in the diagnosis of liver disease through imaging tests, depending on its biodistribution 7 . A recent study in rats showed that splenectomy caused changes in the uptake of 99mTcphytate by the liver, coinciding with deterioration of liver function 13 .…”
Section: Discussion Discussion Discussion Discussionmentioning
confidence: 99%
“…Biodistribution to the liver and bone marrow has shown good correlation with the severity of liver diseases such as cirrhosis and fibrosis of the organs and its prognosis. Thus, quantification of the uptake of 99m Tc-sodium phytate serves as an excellent index of liver function (Groshar et al, 2002;Pereira et al, 2008).…”
Section: Introductionmentioning
confidence: 99%